A Mineralocorticoid Receptor Deficiency in Myeloid Cells Reduces Liver Steatosis by Impairing Activation of CD8+ T Cells in a Nonalcoholic Steatohepatitis Mouse Model - Muñoz-Durango, Natalia; Arrese, Marco; Hernández, Alejandra; Jara, Evelyn; Kalergis, Alexis M.; Cabrera, Daniel (Frontiers in Immunology, 2020)
Background & Aims. The mineralocorticoid receptor (MR) and renin-angiotensin-aldosterone system (RAAS) are implicated in non-alcoholic liver fatty disease (NALFD). However, inflammatory mechanisms linking MR and RAAS with disease pathology remain unclear. Here we aimed to evaluated the contribution of myeloid MR to the inflammatory response in an animal model of non-alcoholic steatohepatitis (NASH), induced with a methionine-choline deficient diet (MCD). Methods: mice with a conditional deficiency of MR in myeloid cells (MyMRKO) and their counterpart controls (LM/WT) were fed for 18 days with MCD or chow diet, respectively . Serum levels of aminotransferases and aldosterone levels were measured and hepatic steatosis, inflammation and fibrosis scored histologically. Hepatic triglyceride content (HTC) and hepatic mRNA levels of pro-inflammatory pro-fibrotic-associated genes were also assessed. Deep flow cytometric analysis was used to dissect the immune response during NASH development. Results: MyMRKO mice fed with an MCD diet exhibited reduced hepatic inflammation and lower HTC than controls. Absolute number and percentage of liver inflammatory infiltrate cells (except for CD8+T lymphocytes) were similar in both MyMRKO and control mice fed with an MCD diet but expression of the costimulatory molecule CD86 by dendritic cells and the CD25 activation marker in CD8+ T cells were significantly reduced in MyMRKO. Conclusions: proinflammatory cells are functionally suppressed in the absence of MR. We hypothesized that loss of MR in myeloid cells reduces lipid accumulation in the liver, in part through modulating the adaptive immune response, which is pivotal for the development of steatosis.